THE EFFECTIVENESS OF USING COMPUTER GAME âFAST HANDSâ TO IMPROVE STUDENTSâ VOCABULARY MASTERY FOR JUNIOR HIGH SCHOOL (A Quasi Experimental Research at the Eighth Grade Students of SMP Negeri 1 Muntilan in the Academic Year of 2014/2015) - Trihandayani, Retno; Sofwan, Ahmad (ELT Forum: Journal of English Language Teaching, 2016)
This study was a quasi-experimental research aimed at finding out whether computer game âFast Handsâ effectively improve studentsâ vocabulary or not. The population of this study were 192 students from the eighth grade of SMP Negeri 1 Muntilan in the academic year 2014/2015. Of this population, two classes were chosen as the experimental group (VIII-B) and the control group (VIII-F) consisting of 24 students for each group. Thus, there were 48 students as the samples. Based on the result of the analysis, it is shown that the studentsâ progress in mastering vocabulary for both groups is good after they were given the treatment. It is shown from the different means result in the experimental group, that is from 66.46 in the pre-test to 84.79 in the posttest. Thus, it has 18.33 in difference. In the control group the difference between the two means is 13.54. 65.83 in the pre-test and 79.37 in the posttest. To check whether the treatment significantly influenced studentsâ vocabulary, the t-test formula was used. Based on the result of the computation, the t-value is 2.237. This result was consulted with the critical value on the t-table with 5% alpha level of significance and 40 degrees of freedom by using interpolation. Based on the result of interpolation, the critical value is 2.015. Since t-value is higher than t-table (2.237 > 2.015) it can be concluded that computer game âFast Handsâ effectively improve studentsâ vocabulary compared to the Word Lists Strategy. Thus, it is suggested that the teachers may use computer game âFast Handsâ in their teaching practice especially in improving studentsâ vocabulary.